Báo cáo Kết quả thực hiện Nghị quyết số 75/2022/QH15 ngày 15/11/2022 của Quốc hội, Nghị quyết số 109/2023/QH15 ngày 29/11/2023 của Quốc hội - Bộ Nội vụ (2024)
Toàn văn Báo cáo Kết quả thực hiện Nghị quyết số 75/2022/QH15 ngày 15/11/2022 của Quốc hội, Nghị quyết số 109/2023/QH15 ngày 29/11/2023 của Quốc hội.